Load Flow Study of Togo and Benin Transmission Power Network by the Newton-Raphson Method. - CHETANGNY, Patrice Koffi; MEDEWOU, Mawuena; Aredjodoun, Jacques G.; CHAMAGNE, Didier; BARBIER, Gérald; HOUNDEDAKO, SOSSOU; VIANOU, Antoine (My University, 2022)
Within the framework of the Economic Community of West African States (ECOWAS) countries power networks interconnection project carried by the West African Power Pool (WAPP), operating guidelines have been defined by WAPP and ECOWAS Regional Electricity Regulatory Authority (ERERA) to ensure efficient operation of the interconnected network. Each operator is obliged to comply with these directives to guarantee the stability and reliability of energy supply to ECOWAS countries. The purpose of this paper is to carry out the study of the power flow on the existing Togo and Benin power transmission network and to propose solutions for compliance with the requirements relating to the voltage level required on the interconnection lines or at connection points with neighboring power network operators. The dynamic stability of generators will also be studied to assess the behavior of the network during major disturbances. CEB (Communauté Electrique du Bénin in french) is the power transmission network operator of the Republic of Togo and the Republic of Benin. After the inventory of CEB transmission and production infrastructure and the consumption report, the model of CEB power network is produced as well as the single-line diagram. The power flow calculation is performed with the Newton-Raphson algorithm and the node voltages were calculated using the Cyme software. From the voltage values obtained at the various nodes and depending on the behavior of each generator, solutions are proposed to improve the voltage plan of the power network in accordance with the recommendations of the Regulatory Authority.
Keywords: Cyme Software; Model; Power Network; Stability